Avaliação de métodos analíticos de solo para estimar a necessidade de calagem - Borges, Ana Lúcia; Braga, José Mário; Defelipo, Braz Vitor; Ribeiro, Antônio Carlos; Lima Thiébaut, José Tarcísio (Revista Ceres, 2025)
Several laboratory methods for estimating liming requirements were compared using four acid soils from the State of Bahia and five soils from the State of Minas Gerais, Brazil. The methods used were the following: base saturation, Woodruff, SMP pH 6.0, Ca(OAc)2 pH 7.0, exchangeable aluminum, exchangeable aluminum and calcium plus magnesium, organic matter to raise the pH to 6.0, and organic matter to raise the pH to 6.5. The liming requirements obtained by these methods were compared with the liming requirement indicated by CaCOj3 incubation used as standard reference. All methods were significantly correlated with the incubation method. As might be expected, the liming requirement of acid soils based on exchangeable Al did not show a simple linear relationship with the buffer methods.